Scaling of erythrocyte shape and nucleus size among squamate reptiles: reanalysis points to constrained, proportional rather than adaptive changes - Bury, Stanisław; Kratochvíl, Lukáš; Starostová, Zuzana (Royal Society open science, 2023)
Small erythrocytes might be beneficial for blood rheology, as they contribute less to blood viscosity than large erythrocytes. We predicted that rheological disadvantages of larger erythrocytes could be alleviated by relatively smaller nucleus size in larger cells allowing higher flexibility and by more elongated shape. Across squamate reptiles, we found that species with larger erythrocytes tend to have smaller ratio of nucleus size to cell size (N : C ratio), but that larger erythrocytes tend to be rounder, not more elongated. Nevertheless, we document that in fact nucleus area changes with erythrocyte area more or less linearly, which is also true for the relationship between cell length and cell width. These linear relationships suggest that nucleus size and cell size, and cell width and cell length, might be constrained to largely proportional mutual changes. The shifts in widely used N : C ratio and elongation ratio (cell length/cell width) with cell size might be misleading, as they do not reflect adaptive or maladaptive changes of erythrocytes, but rather mathematically trivial scaling of the ratios of two variables with a linear relationship with non-zero intercepts. We warn that ratio scaling without analyses of underlying patterns of evolutionary changes can lead to misinterpretation of evolutionary processes.
Keywords: reptiles; erythrocytes; N : C ratio; scaling; cell size; cell shape